Efficiency assessment of the household water use - Jorge, C. (2015)
The aim of the current thesis is the development and testing of a comprehensive methodology to assess the overall households' water use efficiency in indoor domestic water use. This methodology comprises an efficiency evaluation based on efficient patterns, peer comparison and water devices performance. he proposed methodology is composed of three main modules: Module 1. Efficient patterns comparison, Module 2. Peer comparison and Module 3. Evaluation based on performance indices of water devices. The three modules should be applied in a complementary way in order to assess most aspects of water efficiency in the household, but can also be applied independently, as each module returns an individual different type of assessment. The methodology was applied to a case study composed of 43 households, mostly located in the Lisbon urban area and surrounding municipalities, corresponding to approximately 100 persons. All households have extensive measurements and detailed event records of all indoor water uses, and were surveyed to collect information on their socio-demographic characteristics and on the existing water devices in the households (WC, shower, taps, dishwasher and washing machine). The methodology was further tested with an additional small case study carried out with three volunteer consumers. The development of a systematic and detailed methodology for the assessment of domestic consumers’ behaviour both in terms of their own consumption and their level of efficiency relatively to their peers constitutes the main novel contribution of this work. This efficiency assessment allows the identification of potential savings and, thus, the methodology enables the promotion of a more efficient use of water by domestic consumers. Furthermore, it is also useful for the water utilities to optimize the supply systems operation and to improve the quality of service through a better knowledge of consumption profiles.